Neural tube defects in a war-torn Tigray regional state of Ethiopia: a retrospective study of 54,626 deliveries - Birhane Alem Berihu; Afework Mulugeta; Tony Magana; Masresha Tessema; Tafere Gebreegziabher; Yibrah Berhe; Abadi Leul Welderufael; Hayelom Kebede Mekonen (BMC Pregnancy and Childbirth)
Abstract Background The Tigray region of Ethiopia has a significantly high prevalence of neural tube defects (NTDs), ranging from 1.31 to 2.15% of total births. The prevalence has worsened due to ongoing regional war and conflict since October 2020. This study aims to assess NTD prevalence in these challenging conditions. Methods This institution-based, retrospective cross-sectional study was conducted across 11 public hospitals in the Tigray region. The study reviewed all delivery records from October 2020 to December 2023. Data were collected from hospital records, focusing on cases of neural tube defects (NTDs) and relevant maternal and neonatal characteristics. This retrospective analysis aimed to identify the prevalence of NTDs, as well as factors contributing to their occurrence. The data analysis involved using SPSS version 27 for comprehensive data management and statistical evaluation. Descriptive statistics provided an overview of the data, while binary logistic regression offered insights into the factors associated with neural tube defects. The results were systematically presented in both textual, tabular, graph formats to facilitate understanding and interpretation. Results Out of 54,626 delivery records, 1,612 cases of NTDs were identified (1,434 NTD cases and 178 isolated hydrocephalus cases). The specific birth prevalence of NTDs was 262.5 per 10,000 (95% CI, 249.1-276.5 per 10,000), with NTDs being the predominant cause of stillbirths. Anencephaly (136.6 per 10,000), spina bifida (110.6 per 10,000) and encephalocele (15.4 per 10,000) were the most common defects. Risk factors for NTDs include maternal age (20–29 years), rural residency, first pregnancies, a history of early neonatal death, lack of folic acid and multivitamin use, as well as neonatal factors like stillbirth, male sex, and preterm birth. Conclusion This study reveals the alarmingly high prevalence of neural tube defects (NTDs) in the Tigray region, with a birth prevalence of 262.5 per 10,000 births. Anencephaly, spina bifida, and encephalocele were common, contributing to stillbirths. Risk factors include maternal age (20–29), rural residency, first pregnancies, lack of folic acid and multivitamins, and neonatal factors like male sex and preterm birth. The findings stress the need for public health interventions, including folic acid awareness, better prenatal care, maternal nutrition research, stronger health systems, and a national surveillance system to prevent birth defects.